Frithjof Schuon dan Filsafat Perenial - Hamid Nasuhi (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2002)
The study of religion has evolved significantly over time, generally divided into two main approaches: normative and empirical. Theology and philosophy of religion belong to the normative category, while sociology of religion, psychology of religion, and history of religion fall under the empirical category. However, both approaches face criticism: the normative approach is often seen as overly dogmatic, while the empirical approach tends to reduce religion to a purely anthropological phenomenon. In response to these limitations, a new orientation in religious studies has emerged—one that seeks a more sympathetic understanding of different faiths. While phenomenology offers an approach to grasping religious experiences, it does not necessarily uncover the deeper unity underlying religious diversity. This is where perennial philosophy comes into play. One of the foremost scholars devoted to the perennialist approach in modern times is Frithjof Schuon. His works cover a wide range of religious traditions, from Christianity to Native American spirituality, from Islam to Japanese Shintoism. Unlike many Western scholars who focus primarily on the exoteric, empirical aspects of religion, Schuon begins with the esoteric essence of religious doctrines and symbols before examining their exoteric expressions. This method is evident in his three major works on Islam: Understanding Islam, Dimensions of Islam, and Islam and the Perennial Philosophy.